Attitudes and personality of farm managers and association with cow culling rates and longevity in large-scale commercial dairy farms. (January 2022) - Rilanto, Triin; Viidu, Dagni-Alice; Kaart, Tanel; Orro, Toomas; Viltrop, Arvo; Emanuelson, Ulf; Ferguson, Eamonn; Mõtus, Kerli
Abstract: The farmer has the central role in determining cow culling policies on their farm and thus affecting cow longevity. The present study aimed to examine farm managers´ satisfaction, attitudes, personality traits and analyse the associations with dairy cow culling and longevity in large commercial dairy farms. Farm managers of 116 dairy herds rearing at least 100 cows in freestall barns were included. A questionnaire for the farm managers registered personal background information of respondent and included statements capturing their satisfaction, opinions and attitudes regarding dairy cow culling and longevity, farming in general, and a Ten Item Personality Inventory scoring. For each herd, the last 12 months cow culling rate (CR, excluding dairy sale) and herd mean age of culled cows (MAofCC) was obtained from the Estonian Livestock Performance Recording Ltd. A K-mean clustering algorithm was applied to subgroup farm managers based on their attitudes, opinions and personality traits. The yearly mean herd CR was 33.0% and MAofCC was 60.6 months. Farm managers´ were mostly dissatisfied with cow longevity and culling rates in their farms. Dissatisfaction with culling rates and longevity, priority for producing high milk yields over longevity and production-oriented attitude was associated with high culling rates and poor longevity. Farm managers' personality had an effect on herd culling rates and their attitudes explained one third of the variability of culling rates and longevity. Explaining the economic consequences of high culling rates and decreased longevity, improving the visibility of these parameters together with benchmarking could bring these issues into focus. Highlights: Farm managers were mostly dissatisfied with dairy cow longevity. Improving cow longevity was considered economically profitable by farm managers. Prioritizing high milk yields over longevity reversed to cow longevity. Production-oriented attitude was associated with high culling rates and poor longevity. Farm managers´ attitudes explained one third of variability of culling rates and longevity.